Gluten replacement and starch reduction in producing gluten free bread - Ren, Yi (2020)
The main target of the project is to investigate gluten replacement and starch replacement in gluten free products for the purpose of dealing with gluten intolerance, obesity, diabetes, and meeting the public requirement of healthy diets. The focus of the first part is on psyllium seed husk powder (PSY), whose main compound is heteroxylan. Both whole PSY and fractions (by temperature) were investigated. Fractions show distinct rheological properties, arabinose/xylose ratios and sidechain substitutions. Two hypotheses were proposed focusing on either chemical and molecular structural properties or hierarchical molecular conformations.